Evaluasi Pemeliharaan Lanskap pada Kawasan Taman Candi Kabupaten Ngawi, Jawa Timur - Caesar Tegar Prihanggo; I Made Sukewijaya (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The Taman Candi is included in the category of active green open space (GOS). Based on this, it is necessary to carry out good maintenance aimed at maintaining the quality of facilities, both softscape and hardscape in the park. Maintenance in Taman Candi Ngawi Regency refers to the park maintenance standards by Arifin and Arifin (2005). Data processing was carried out using a quantitative method, namely using a work capacity calculation formula, aimed at measuring the suitability of work and worker effectiveness from the maintenance of the Taman Candi Ngawi Regency. The management of the Taman Candi in Ngawi Regency does not have a written maintenance schedule, so maintenance activities are carried out flexibly or according to the conditions in the field, and there are several activities that have not been carried out, the results show that there is still work that is not ideal from the work capacity and exceeds the ideal value in accordance with the standard of maintenance work capacity of Arifin and Arifin (2005). This is due to the lack of knowledge of workers about good and correct maintenance activities, the absence of a written schedule from the manager, and the lack of availability of tools.